PENDAMPINGAN HUKUM UNTUK PELAKU UMK DALAM PENYELESAIAN PERKARA UTANG PIUTANG: MENUJU USAHA YANG BERKELANJUTAN - Muhammad Kurniawan Budi Wibowo; Fajri, Aditya (Tahta Media Grup, 2024)
This community service activity aims to provide legal assistance to Micro and Small Enterprise (MSE) actors in resolving debt and credit cases that often become obstacles to business sustainability. The activity approach includes legal consultation, preparation of legal documents, and mediation, which are carried out using participatory methods to ensure the active involvement of participants. The activities were implemented in October 2024 by LBH Mambaul Ulum Surakarta, with the main locations in Surakarta and Ponorogo. The results showed a significant positive impact, with MSE actors gaining a better understanding of their legal rights and obligations, as well as effective solutions in resolving disputes. Mediation resulted in faster and more economical settlements compared to litigation. Legal education also improved participants' legal literacy, enabling them to deal with legal issues more confidently. However, there were some challenges, such as limited time for in-depth consultations and the need for stronger synergies with relevant financial institutions. This activity concluded that community-based legal assistance is effective in supporting MSE business sustainability. Recommendations were made to expand the scope of the programme and strengthen cross-institutional collaboration to provide greater access to justice for MSE actors.